IDDF2020-ABS-0185 Pharmacoeconomic evaluation of bevacizumab or cetuximab combined chemotherapy for advanced colorectal cancer in real world. (18th November 2020) - Hua, Yunqi; Wang, Chenlin; Zhao, Cuiyun; Cao, Kun; Jin, Yunjian; Li, Xi; Tan, Yaqin; Li, Min; Zhao, Meili
Abstract : Background: Clinical first-line data are needed to support the economic evaluation of drugs in the real world. We will see the efficacy of two targeted drugs (Bevacizumab versus Cetuximab) combined with chemotherapy for advanced colorectal cancer and the economics of evaluating two targeted drugs in real-world. Methods: Between 2018 and 2020, 68 patients were treated with targeted drugs (Bevacizumab versus Cetuximab) combined with chemotherapy. All patients met the diagnostic requirements of advanced colorectal cancer. 1. Cases were divided into 2 groups: Group A received bevacizumab plus chemotherapy(40cases), and Group B received Cetuximab plus chemotherapy(28cases). 2. Treatment programme: Group A: Bevacizumab 5 mg/Kg combination chemotherapy (FOLFOX/FOLFIRI); Group B: K-ras Gene Wild type colorectal cancer patients, Cetuximab 400 mg/m 2 in the first week, then 250 mg/m 2 per week, Combined chemotherapy (FOLFOX/FOLFIRI), 14 days for 1 cycle. Evaluation of efficacy and economics after 4 cycles. 3. The establishment of cost: including: drug costs, bed costs, inspection costs, treatment costs, nursing costs. The total cost is the sum of the above costs. 4. The short-term curative effect evaluation is based on RECIST. Cost-effectiveness ratio (c/e) = efficiency/total cost. 5. Statistical Methods All data were analyzed by SPSS 17.0. statistical software; P < 0.05 was statistically significant. Results: The clinical effective rate of Bevacizumab combined with chemotherapy was (12/40)30.0%. The clinical effective rate of Cetuximab combined with chemotherapy was (8/28)28.6%, there was no significant difference between the two groups ( P >0.05) The average cost of Bevacizumab combined chemotherapy group was 11, 500 yuan, and that of Cetuximab group was 29, 800 yuan, the difference was statistically significant( P <0.05); The cost-effectiveness ratio was (0.3/1.15)26.09% in Bevacizumab combined chemotherapy group and (0.28/2.98)9.40% in Cetuximab combined chemotherapy group, the difference was statistically significant( P <0.05). Conclusions: In the real world, Bevacizumab combined chemotherapy and Cetuximab combined chemotherapy have the same clinical efficacy. The former is better in economic evaluation, therefore, Bevacizumab combined with chemotherapy is the first choice for patients with advanced colorectal cancer.